Children and Crime of Pornography (Faculty of Law Universitas Negeri Semarang, 2022)
Children are one of the groups vulnerable to crimes, including sexual crimes and pornography crimes. Cases of pornography crimes involving children as victims are increasingly rampant amid the rapid flow of information and technology. This study aims to analyze child and pornography crimes from the legal and victim protection aspects in Indonesia. This study uses a normative approach by comparing various legal rules and legal theories and victimology related to cases of child crimes and pornography.